Contact Based School Intervention Program: Enhancing Cooperation Intention and Reducing Prejudice toward Roma - Petrík, Juraj; Popper, Miroslav (Studia Psychologica, 2020)
The aim of the paper is to assess the effects of an intervention program derived from contact theory on intergroup attitudes toward the Roma minority. A sample of 150 high school students from two midsized towns were randomly assigned to a control group and an experimental group. Participants in the experimental group attended six sessions of a Junior Project Manager program run by a local organization, which included project management lessons, a lesson on the discriminated minority and positive, cooperative direct contact with the Roma minority in work settings. Participant attitudes were measured prior to and after the intervention program. The intervention program had a positive impact on intergroup attitudes, intergroup trust, approach/avoid tendencies and intended future cooperation. The results indicate this was the first successful attempt to change intergroup attitudes using direct contact in a Slovak context.